2022
DOI: 10.3389/fphar.2022.960037
|View full text |Cite
|
Sign up to set email alerts
|

From kitchen to clinic: Pharmacotherapeutic potential of common spices in Indian cooking in age-related neurological disorders

Abstract: Aging is described as an advanced time-related collection of changes that may negatively affect with the risk of several diseases or death. Aging is a main factor of several age-related neurological disorders, including neurodegenerative diseases (Alzheimer’s disease, Parkinson’s disease, and dementia), stroke, neuroinflammation, neurotoxicity, brain tumors, oxidative stress, and reactive oxygen species (ROS). Currently available medications for age-related neurological disorders may lead to several side effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 283 publications
0
1
0
Order By: Relevance
“…aSyn accumulation and LB formation are major components thought to trigger several cellular pathways that lead to this neuronal loss [ 171 , 173 ]. Although aging is the most significant risk factor for PD [ 38 , 88 , 142 ], lipid balance and their metabolism are emerging as important factors for PD, and will be discussed in the present review.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…aSyn accumulation and LB formation are major components thought to trigger several cellular pathways that lead to this neuronal loss [ 171 , 173 ]. Although aging is the most significant risk factor for PD [ 38 , 88 , 142 ], lipid balance and their metabolism are emerging as important factors for PD, and will be discussed in the present review.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…(Apiaceae), commonly known as cumin, is a popular spice that has been utilized for centuries for its medicinal properties in alleviating a range of symptoms. Although the effects of this plant on anxiety (15), memory loss and stress (16), and age-related neurological disorders (17) have been examined in previous studies, the current research is the first report on the hydroalcoholic extract of cumin and its impact on passive avoidance learning (PAL) in gonadectomized (GDX) male Wistar rats. The study results indicated that GDX reduced PAL, while cumin HAE doses of 50 and 100 mg/kg in the GDX male Wistar rats augmented its incidence.…”
Section: Discussionmentioning
confidence: 99%